Tinjauan Kompatibilitas Konsep Moderasi Beragama Kementerian Agama Republik Indonesia Dengan Wasathiyatul Islam - Rohmadi Rohmadi; Jarman Arroisi; M. Kholid Muslih (Universitas Muhammadiyah Ponorogo, 2022)
The Ministry of Religious Affairs of the Republic of Indonesia compiled the concept of Religious Moderation based on the teachings of various official religions in Indonesia, so that Religious Moderation deserves to be called the middle ideal concept of religion and is expected to overcome extremism and radicalism in the name of religion. The term moderation used by the Ministry of Religion has historically originated from secular (non-religious) culture incorporated into the thinking of Indonesians whose majority of the population has known the term middle with wasathiyah in Islam. This is the importance problem to re-examining whether the concept of Religious Moderation compatible with the concept of wasathiyah in Islam? How is the concept of Religious Moderation of the Ministry of Religious Affairs of the Republic of Indonesia viewed from the concept of wasatiyah in Islam? The research method used is library research with a critical analysis approach. The results of this study include: first, moderation is not the same as wasatiyah; secondly, Religious Moderation when placing itself as a counterradicalism in the view of Islamic wasatiyah has been at another extreme with the dominance of Western thought.